2015
DOI: 10.1021/jacs.5b07932
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Activated Delayed Fluorescence Materials Based on Homoconjugation Effect of Donor–Acceptor Triptycenes

Abstract: Donor-acceptor triptycences, TPA-QNX(CN)2 and TPA-PRZ(CN)2 were synthesized and their emissive properties were studied. They exhibited a blue-green fluorescence with emission lifetimes on the order of a microsecond in cyclohexane at room temperature. The long lifetime emission is quenched by O 2 and is attributed to thermally activated delayed florescence (TADF). Unimolecular TADF is made possible by the separation and weak coupling due to homo-conjugation of the HOMO and LUMO on different arms of the three-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
216
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 351 publications
(223 citation statements)
references
References 33 publications
(28 reference statements)
1
216
1
2
Order By: Relevance
“…14 The mixture was stirred in room temperature for 0.5 h then heating to 60 o C for 4 h. The reaction was terminated by adding 1 mL of water and the liquids were washed by saturated ammonium chloride solution and extracted by dichloromethane. The solvent was volatilized by rotary evaporation and gross product was purified by column chromatography on silica gel (eluent:…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…14 The mixture was stirred in room temperature for 0.5 h then heating to 60 o C for 4 h. The reaction was terminated by adding 1 mL of water and the liquids were washed by saturated ammonium chloride solution and extracted by dichloromethane. The solvent was volatilized by rotary evaporation and gross product was purified by column chromatography on silica gel (eluent:…”
Section: Synthesismentioning
confidence: 99%
“…12 With an extremely small singlet-triplet splitting (∆E ST ), TADF emitter can realize efficient upconversion of non-radiative triplet excitons to radiative singlet excitons via reverse intersystem crossing (RISC) process. [13][14][15][16] Thus, compared with PhOLEDs, the TADF OLEDs can also deliver a full exciton harvesting theoretically, but without heavy metals. 18-21 3 To realize the key point of extremely small ∆E ST s for TADF emitters, minimizing the overlap between the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) in the molecules is essential.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12] Generally, a small singlet-triplet energy splitting (ΔE ST ), which can be realized by spatially separating the overlap between the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) distribution, is required to ensure effective RISC process; [13][14][15][16] meanwhile a certain degree of frontier molecular orbital (FMO) overlap is also necessary to guarantee intrinsically high photoluminescence quantum yield (PLQY). [17][18][19][20] However, the intrinsic tradeoff between these two requirements has to be carefully managed towards designing ideal TADF emitters. [21,22] Numerous attempts to achieve this compromise have revealed that the feasible design strategy is to introduce pre-twisted charge-transfer configuration in donoracceptor (D-A) systems with or without aryl linkage.…”
Section: Introductionmentioning
confidence: 99%
“…[21,22] Numerous attempts to achieve this compromise have revealed that the feasible design strategy is to introduce pre-twisted charge-transfer configuration in donoracceptor (D-A) systems with or without aryl linkage. [13,18,23] Therefore, the suitable selection of electron D, A units and their linking tactics are of vital importance to achieve excellent TADF emitters with near-zero ΔE ST and high PLQY. [6,7,14,20,24] Although promising results have been achieved on TADF emitters with the state-of-art external quantum efficiencies (η ext s) close to those of phosphorescent OLEDs, the further improvement in the device efficiency and stability is still in demand, and the insight into the relationship between the TADF molecular structures and properties is to be deepened.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, efficient reverse intersystem crossing (RISC) process and high fluorescence quantum yield ( Φ F ) are two essential requirements for efficient TADF emitters 1, 5. For the former one, an extremely small singlet‐triplet energy split (Δ E ST ) between lowest singlet excited state (S 1 ) and lowest triplet excited state (T 1 ) is highly desired to up‐convert triplet excitons to singlet excitons through thermal excitation 4, 6, 7, 8, 9, 10. Thus, electron‐donor (D)–electron‐acceptor (A) frameworks with a highly twisted way are generally employed to construct TADF emitters, as they can well isolate highest occupied molecular orbitals (HOMOs) in D moieties and lowest unoccupied molecular orbitals (LUMOs) in A moieties, respectively, resulting in small Δ E ST s and thus effective RISC process 11, 12, 13, 14, 15.…”
mentioning
confidence: 99%